Implementasi Strategi Menggunting Bentuk Geometri untuk Meningkatkan Kemampuan Motorik Halus Anak Usia 4-5 Tahun di Taman Kanak-Kanak - Kustiyowati, Kustiyowati (Universitas Negeri Padang, 2020)
This study aims to improve fine motor skills in children aged 4-5 years through cutting geometric shapes in Raudhatul Ulum Kindergarten Jember. This research is a collaborative classroom action research conducted in 2 cycles. Research subjects in children aged 4-5 years at Kindergarten Raudhatul Ulum Jember with 22 children. Data collection methods in this study used questionnaires and observations. Data analysis techniques using data reduction and data presentation. The average yield in the underdeveloped category is known to be a percentage of 55%, in terms of opening and cutting straight lines 45%. Cut the shape but not on the 50% line. Cut 70% of various geometric shapes. Next shows an increase after the first and second cycles are carried out in the Start Developing category with initial conditions with an average percentage of 55%, in the first cycle an average percentage of 65% and a second cycle an average percentage of 60% and no more percentage of 0%. Developing categories in line with expectations in the initial conditions an average percentage of 45%, in the first cycle an average percentage of 65% and a second cycle an average percentage of 70%. The observations cut geometric shapes from the Very Good Developing category in the initial conditions with an average percentage of 46%, in the first cycle the average percentage is 68% and the second cycle is an average percentage of 86%. Thus efforts to improve fine motor skills through cutting geometric shapes in children aged 4-5 years at Kindergarten Raudhatul Ulum Jember have increased and succeeded.Â Keywords: Strategy to Cut Geometry Shapes, Fine Motor Ability